Cooperation and Competition in Intergenerational Experiments in the Field and the Laboratory - Charness, Gary; Villeval, Marie-Claire (The American economic review, 2009)
There is economic pressure to postpone the retirement age, but employers are still reluctant to employ older workers. We investigate the comparative behavior of juniors and seniors in experiments conducted both onsite with the employees of two large firms and in a conventional laboratory environment with students and retirees. We show that seniors are no more risk averse than juniors and are typically more cooperative; both juniors and working seniors respond strongly to competition. The implication is that it may be beneficial to define additional incentives near the end of the career to motivate and retain older workers.